2010
DOI: 10.1103/physrevb.82.144514
|View full text |Cite
|
Sign up to set email alerts
|

Vortex core transitions in superfluidH3ein globally anisotropic aerogels

Abstract: Core structures of a single vortex in A-like and B-like phases of superfluid 3 He in uniaxially compressed and stretched aerogels are studied by numerically solving Ginzburg-Landau equations derived microscopically. It is found that, although any uniaxial deformation leads to a wider A-like phase with the axial pairing in the pressure-temperature phase diagram, the vortex core states in the two phases in aerogel depend highly on the type of deformation. In a compressed aerogel, the first-order vortex core tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
1
Order By: Relevance
“…This is also consistent with the fact that non-axisymmetric vortices only exist at low temperatures in the present work. Aoyama and Ikeda have reported that a vortex of 3 He-A can be non-axisymmetric under the existence of anisotropic scatterers [39,40]. Their model is different from ours, and the relationship between their and our results considered an important but remaining issue.…”
Section: Resultscontrasting
confidence: 75%
“…This is also consistent with the fact that non-axisymmetric vortices only exist at low temperatures in the present work. Aoyama and Ikeda have reported that a vortex of 3 He-A can be non-axisymmetric under the existence of anisotropic scatterers [39,40]. Their model is different from ours, and the relationship between their and our results considered an important but remaining issue.…”
Section: Resultscontrasting
confidence: 75%